2018
DOI: 10.1523/jneurosci.0515-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of ERK Signaling Rescues Pathophysiology and Behavioral Phenotype Associated with 16p11.2 Chromosomal Deletion in Mice

Abstract: The human microdeletion is one of the most common gene copy number variations linked to autism, but the pathophysiology associated with this chromosomal abnormality is largely unknown. The 593 kb deletion contains the ERK1 gene and other genes that converge onto the ERK/MAP kinase pathway. Perturbations in ERK signaling are linked to a group of related neurodevelopmental disorders hallmarked by intellectual disability, including autism. We report that mice harboring the deletion exhibit a paradoxical elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 62 publications
5
74
0
Order By: Relevance
“…SELE, CALML6, RAF1, SEMA4A). This finding supports existing work suggesting that the Erk1 MAPK pathway, which has been shown to modulate the proliferation of cortical progenitors, may drive phenotypic abnormalities associated with the 16p11.2 CNV 38,59 . Although we detected a decrease in MAPK3 gene expression in all the 16p11.2 deletion lines [ Supplementary Figure 5A], we did not observe any changes in NPC proliferation between wild type and deletion lines indicating that MAPK3 may not influence neocortical progenitor cell proliferation in these 16p11.2 patient lines [Supplementary Figure 4A].…”
Section: Current Investigations Into the Etiology Of Neurodevelopmentsupporting
confidence: 90%
See 1 more Smart Citation
“…SELE, CALML6, RAF1, SEMA4A). This finding supports existing work suggesting that the Erk1 MAPK pathway, which has been shown to modulate the proliferation of cortical progenitors, may drive phenotypic abnormalities associated with the 16p11.2 CNV 38,59 . Although we detected a decrease in MAPK3 gene expression in all the 16p11.2 deletion lines [ Supplementary Figure 5A], we did not observe any changes in NPC proliferation between wild type and deletion lines indicating that MAPK3 may not influence neocortical progenitor cell proliferation in these 16p11.2 patient lines [Supplementary Figure 4A].…”
Section: Current Investigations Into the Etiology Of Neurodevelopmentsupporting
confidence: 90%
“…Interestingly, transcriptional and phenotypic abnormalities have also been observed in hiPSC-derived cortical neural stem cells derived from individuals with idiopathic ASD 36,37 . The 16p11.2 deletion has widespread effects on signaling pathways that underpin critical neural progenitor functions, including proliferation and fate choice 38 , yet 16p11.2 CNV-related alterations in gene expression patterns have not been examined in early neuroepithelial precursors (radial glia), the stem and progenitor cells of the developing cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome profiling of lymphoblastoid cell lines of 16p11.2 CNV human carriers identified expression dysregulation of neuronal-related gene in deletion, but not in duplication (Luo et al, 2012). Dysregulation of ciliopathy genes (Migliavacca et al, 2015), ERK/MAPK signaling (Pucilowska et al, 2018;Pucilowska et al, 2015), and metabotropic glutamate receptor 5 (mGluR5)-dependent synaptic plasticity and protein synthesis (Tian et al, 2015) in mouse models were all shown to play a role. Despite the progress made with regard to understanding of the general mechanisms disrupted by the 16p11.2 CNV, the question of how 16p11.2 variants impact early human brain development remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…The ERK/MAPK cascade is a commonly utilized intracellular signaling pathway that is dynamically activated during embryogenesis and in adulthood. In the embryonic ventricular zone, neural progenitors typically show high levels of P-ERK1/2 relative to immature post-mitotic neurons (Pucilowska et al, 2018; Stanco et al, 2014). In adult cortices, elevated P-ERK1/2 labeling is enriched in a heterogeneous set of excitatory PNs, primarily in layer 2, and plays a critical role in long-range PN development (Cancedda et al, 2003; Gauthier et al, 2007; Holter et al, 2019; Pham et al, 2004; Pucilowska et al, 2012; Suzuki et al, 2004; Xing et al, 2016).…”
Section: Resultsmentioning
confidence: 99%